2017
DOI: 10.3732/ajb.1600227
|View full text |Cite
|
Sign up to set email alerts
|

Anchored phylogenomics improves the resolution of evolutionary relationships in the rapid radiation ofProteaL.

Abstract: Species tree methods using hundreds of nuclear loci provided strong support for many previously unresolved relationships in the radiation of the genus Protea. In cases where support for particular relationships remains low, these appear to arise from few informative sites and lack of information rather than strongly supported disagreement among gene trees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 68 publications
1
66
0
Order By: Relevance
“…The application of the NGS techniques has enabled access to large amounts of data and has helped resolve the basal polytomies in certain groups of organisms where traditional Sanger approaches using analyses of multiple‐genes failed (e.g., Graminoids, Leseber & Duvall, ; Rhinoceroses, Willerslev et al, ; Pentapetaleae, Moore et al, ; Paserida, Nabholz et al, ; Neoaves, Pacheco et al, ; Malpighiales, Xi et al, ; Commelinids, Barrett et al, ; Guenons, Guschanski et al, ; Zingiberales, Barrett et al, , Sass et al, ; Ipomeeae, Eserman et al, ; Arundinarieae, Ma et al, ; Apocynaceae, Straub et al, ; Asteraceae, Mandel et al, ; Goodeniaceae, Gardner et al, ; Columbiforms, Soares et al, ; Vitales, Zhang et al, , Wen et al, ; Eupolypod II Ferns, Wei et al, ; Hippeastreae, García et al, ; Protea , Mitchell et al, ). Most of these studies concluded in favor of the radiation hypothesis, since the NGS analysis of complete chloroplast genomes and large nuclear data sets yielded short deep branches (Leseber & Duvall, ; Moore et al, ; Nabholz et al, ; Xi et al, ; Guschanski et al, ; Straub et al, ; Mandel et al, ; Gardner et al, ; Sass et al, ; Soares et al, ; Zhang et al, ; García et al, ; Mitchell et al, ) or non‐fully resolved trees (Willerslev et al, ; Barrett et al, , ; Ma et al, ; Wei et al, ). A previous phylogenetic study based on seven DNA regions proposed a burst of diversification for the origin of the Asian Palmate group (Valcárcel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The application of the NGS techniques has enabled access to large amounts of data and has helped resolve the basal polytomies in certain groups of organisms where traditional Sanger approaches using analyses of multiple‐genes failed (e.g., Graminoids, Leseber & Duvall, ; Rhinoceroses, Willerslev et al, ; Pentapetaleae, Moore et al, ; Paserida, Nabholz et al, ; Neoaves, Pacheco et al, ; Malpighiales, Xi et al, ; Commelinids, Barrett et al, ; Guenons, Guschanski et al, ; Zingiberales, Barrett et al, , Sass et al, ; Ipomeeae, Eserman et al, ; Arundinarieae, Ma et al, ; Apocynaceae, Straub et al, ; Asteraceae, Mandel et al, ; Goodeniaceae, Gardner et al, ; Columbiforms, Soares et al, ; Vitales, Zhang et al, , Wen et al, ; Eupolypod II Ferns, Wei et al, ; Hippeastreae, García et al, ; Protea , Mitchell et al, ). Most of these studies concluded in favor of the radiation hypothesis, since the NGS analysis of complete chloroplast genomes and large nuclear data sets yielded short deep branches (Leseber & Duvall, ; Moore et al, ; Nabholz et al, ; Xi et al, ; Guschanski et al, ; Straub et al, ; Mandel et al, ; Gardner et al, ; Sass et al, ; Soares et al, ; Zhang et al, ; García et al, ; Mitchell et al, ) or non‐fully resolved trees (Willerslev et al, ; Barrett et al, , ; Ma et al, ; Wei et al, ). A previous phylogenetic study based on seven DNA regions proposed a burst of diversification for the origin of the Asian Palmate group (Valcárcel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is often difficult to estimate phylogenetic relationships in rapid radiations (Knowles & Chan, ). In earlier work, we used an anchored phylogenomics approach (Lemmon, Emme, & Lemmon, ) to sequence almost 500 nuclear genes conserved across all angiosperms (Buddenhagen et al., In Review) and built a robust and highly resolved phylogeny for 59 Protea species (Mitchell, Lewis, Moriarty Lemmon, Lemmon, & Holsinger, ; Buddenhagen et al. In Review).…”
Section: Methodsmentioning
confidence: 99%
“…To ensure that our results are robust in the face of both phylogenetic and trait/climate uncertainty, we compared results of analyses using the “best” tree from the program ASTRAL‐II (Figure ; Mirarab & Warnow, ) or 100 bootstrap replicates from the ASTRAL‐II analysis of Mitchell et al. () with either the posterior mean of the trait/climate distribution or 100 random samples from the HPD distribution. We thus have a two‐by‐two table comparing one measure (mean trait on the best tree), 100 measures (mean trait on 100 bootstrap trees; 100 observations of traits on best tree), or 10,000 measures (100 observations of traits on 100 bootstrap trees).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A well‐resolved phylogeny is essential for understanding the evolution and biogeography of maples in the world and has been made possible by the development of anchored phylogenomics (Lemmon et al, ) that enabled orthologous data to be collected efficiently across broad taxonomic groups. The DNA sequence data from multiple nuclear loci have been used successfully in constructing solid phylogenetic frameworks for large plant genera (Buddenhagen et al, ; Mitchell et al, ; Wanke et al, ). Therefore, the main objectives of the study were to generate a robust phylogeny of Acer for the first time using the anchored phylogenomics data and to explore implications of the well‐resolved phylogeny for the previous biogeographic hypotheses.…”
Section: Introductionmentioning
confidence: 99%